Bronchodilator and cardiac effects of isoprenaline, orciprenaline, and salbutamol aerosols in asthma. Issue 248 (August 1971) - Milner, A. D.; Ingram, D.
Abstract : The bronchodilator and cardiac effects of 0·5% isoprenaline, 2·5% orciprenaline, and 0·5% salbutamol, and a placebo solution inhaled as a nebulized mist from a Wright nebulizer were compared with the help of 12 asthmatic children. All three active drugs produced similar relief of bronchoconstriction, but salbutamol was followed by only a 13% increase in heart rate compared with 26% after orciprenaline and 29% after isoprenaline, and only a 9% increase in systolic blood pressure compared to 13% after orciprenaline and 15% after isoprenaline.